The Influence of Financial Literacy, Financial Attitudes, and Personality on Financial Management Behavior of SME in Banyumas Regency - Rahmawati, Ika Yustina; Wahyu, Rizky Ananda; Pandansari, Tiara; Hapsari, Ira; Inayati, Nur Isna (LP3M Universitas Putra Bangsa, 2024)
This study aims to analyze the effect of financial literacy, financial attitudes, and personality on financial management behavior. This study uses a quantitative method, the sampling technique is Non-Probability Sampling, purposive sampling approach, the number of samples is 100 respondents. The data analysis technique used in this study is descriptive statistical test, classical assumption test, multiple linear regression test, model fit test, and hypothesis testing with the analytical tool used is SPSS. The results of the analysis show that financial literacy and personality partially have a positive and significant effect on financial management behavior. Meanwhile, financial attitudes have a negative and significant effect on financial management behavior.